How multiple interviews and interview framing influence the development and maintenance of rapport - Weiher, Lynn (Psychology, crime & law, 2025)
Information obtained from investigative interviews is crucial for police to develop leads, advance investigations and make effective decisions. One well-endorsed approach for eliciting detailed and accurate information is building rapport between the interviewer and interviewee. While familiarity and communicative tone are predicted determinants of rapport, the effects of repeated exposure to an interviewer, as well as interview framing, on rapport has rarely been tested. In two simulated suspect interview experiments, we tested whether established rapport is maintained during a second interview with the same interviewer (Experiment 1) and how accusatory and humanitarian interview framings impact the development of rapport (Experiment 2). We also tested, across both experiments, whether nonverbal mimicry can be a proxy for measuring rapport. We found evidence suggesting that rapport, once established, is carried over to subsequent meetings, and that it is possible to build rapport even when it was poorly established in the initial interview. We also found that an accusatory interview framing was associated with lower rapport than a humanitarian interview framing, and that interview framing affected nonverbal mimicry between interviewer and interviewee. Contrary to our expectations, mimicry did not correlate with an existing measure of rapport.